Managing courtesy stigma: women and relationships with men in prison. Issue 3 (3rd July 2021) - DeShay, Rashaan A.; Vieraitis, Lynne M.; Copes, Heith; Powell, Zachary A.; Medrano, Justine
ABSTRACT: The stigma associated with incarceration is well documented. Less attention has been directed to the impact of this stigma on those in romantic relationships with partners who are incarcerated (i.e. courtesy stigma). Using semi-structured interviews with 12 women involved in romantic relationships with men who were incarcerated, we explore whether they experienced courtesy stigma and if so, how they managed it. The women said they experienced courtesy stigma from others, including friends and family. In response, participants either avoided interactions with those they thought would judge them (by withholding information or severing ties) or by fully embracing the relationships (pointing to their benefits). These management techniques allowed participants to have a sense of agency in their decisions. Considering the importance of healthy relationships in promoting desistance from criminal behavior, examining the management of courtesy stigma from the perspective of the un-incarcerated partner may increase our understanding of these relationships on reentry.